Identifying climate–agriculture–gender inequality hotspots can help target investments and make women drivers of climate resilience - Puskur, Ranjitha; Lecoutere, Els (CGIAR GENDER Impact Platform, 2022)
"Key Messages - Women in food systems tend to be more negatively impacted by climate risks than men as they are more dependent on agriculture as well as more constrained in responding and adapting to changes in climate because of structural socio-economic inequalities. - Identifying climate–agriculture–gender inequality hotspots, where climate hazards converge with large concentrations of women participating in food systems and significant structural gender inequalities, enables allocating scarce resources to most-at-risk populations. - Women’s vulnerability to climate risk is highly contextual; this methodology to identify hotspots can be applied to identify subnational hotspots within countries. - When root causes of women’s excess risk to climate change impacts are addressed, women can be agents of change in building climate resilience."